SWOT Analysis in Improving Competitiveness of Cleanwear Shoe Washing Services - Gheasya Nonik Indrasari; Lia Nirawati (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to improve the competitiveness of Cleanwear shoe washing services Surabaya City branch through SWOT analysis, namely strengths, weaknesses, opportunities, threats. This study used a qualitative descriptive approach, and data collection was carried out through data narratives, namely interviews (oral and written), observation, and documentation. The principle of suitability and adequacy is based on the research of informants. There are five informants who serve as the basis of this study. Results show that the current state of Cleanwear is in quadrant 1, which indicates that the company is in a favorable condition because the company has the ability to select multiple opportunities at this time to enable optimal expansion, growth, and progress. In this condition, the Surabaya branch of Cleanwear faces a huge market opportunity. The strategy that must be carried out is to minimize internal problems so that it can seize better market opportunities.